The search for potential antivirals of SARS-COV-2 spike protein: A virtual screening study / Basma Mohamed Rehan - Basma , Mohamed Rehan (2023)

(untitled)
The COVID-19 outbreak caused by a new coronavirus emerged in December 2019 and has since spread across the globe. The spike protein of SARS-CoV-2 is the main target in research therapeutic to control viral infection and pathogenesis. Inhibition of spike protein can cause structural and functional changes, subsequently blocking the entry of the coronavirus into host cells. The in-silico virtual screening is an alternative to traditional screening in drug discoveries with a significant reduction to cost and time. This study aimed to screen NuBBE database to identify a potential inhibitor against spike protein. A library of natural-based compounds was docked on spike protein obtained from the protein data bank. Ten compounds were selected based on their binding affinity for further analysis. The ligand bound in close proximity to the positive control binding site was chosen as a promising compound and subjected for molecular dynamics simulation and ADMET scoring. the result indicated that (spike-Lig126) has a stable conformation with hydrogen bonds formation and ADMET properties. The inhibitory properties of Lig126 require further investigation in the laboratory to prove it and it could finally be upgraded to an anti-SARS drug.